2016
DOI: 10.1016/j.ajhg.2016.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing Identifies Biallelic MSH3 Germline Mutations as a Recessive Subtype of Colorectal Adenomatous Polyposis

Abstract: In around 30% of families with colorectal adenomatous polyposis, no germline mutation in the previously-implicated genes APC, MUTYH, POLE, POLD1, or NTHL1 can be identified, although a hereditary etiology is likely. To uncover further genes with high-penetrance causative mutations, exome sequencing of leukocyte DNA from 102 unrelated individuals with unexplained adenomatous polyposis was performed. We identified two unrelated individuals with differing compound-heterozygous loss-of-function germline mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
175
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(183 citation statements)
references
References 80 publications
3
175
1
4
Order By: Relevance
“…Biallelic MSH3 mutations have also been identified as predisposing to MSI CRC, however this occurs in longer repeats than is currently investigated by conventional MSI testing. However, the increasing use of NGS may eventually preclude this issue (Adam et al, 2016).…”
Section: "Lynch-like Syndrome" and Novel Aetiologies Of Msi Colorectamentioning
confidence: 99%
See 1 more Smart Citation
“…Biallelic MSH3 mutations have also been identified as predisposing to MSI CRC, however this occurs in longer repeats than is currently investigated by conventional MSI testing. However, the increasing use of NGS may eventually preclude this issue (Adam et al, 2016).…”
Section: "Lynch-like Syndrome" and Novel Aetiologies Of Msi Colorectamentioning
confidence: 99%
“…For example NGS approaches has helped identify suspected LLS patients that actually have Lynch syndrome, as some tumours may be due to constitutional mutations in DNA MMR genes that are not detectable by standard testing (Rodriguez-Soler et al, 2013). NGS testing has also identified somatic mutations coupled with LOH (Geurts-Giele et al, 2014;Haraldsdottir et al, 2014;Kang et al, 2015;Rodriguez-Soler et al, 2013;Sourrouille et al, 2013) and constitutional mutations in additional genes as causes of dMMR (Adam et al, 2016;Castillejo et al, 2014;Cohen et al, 2016;Haraldsdottir et al, 2014;Palles et al, 2013;Segui et al, 2015;Syngal et al, 2015;Weren et al, 2015).…”
Section: The Role Of Next Generation Sequencing In Determining Mmr Stmentioning
confidence: 99%
“…36 Recent data have suggested that biallelic MSH3 germline mutations are a recessive subtype of colorectal adenomatous polyposis. 37 During the 2017 NCCN Guidelines update, MSH3 was added to a list of genes commonly included on multigene panels (see GENE-5; page 1468). However, given available data, the panel agreed that the strength of evidence linking MSH3 to increased CRC risk is not currently well established.…”
Section: Msh3 Mutationsmentioning
confidence: 99%
“…These include bone and soft-tissue sarcomas, genitourinary cancer, and other cancers occurring more frequently from the latter part of the first decade of life. Second is the encouraging data from the implementation of WBMRI in patients with Li-Fraumeni syndrome (3,25) and the high feasibility of the tool in children who do not require anesthesia, which give strong consideration for its use in CMMRD. The current suggestion is to implement WBMRI once a year at 6 year of age or when anesthesia is not needed.…”
Section: Surveillance Protocolmentioning
confidence: 99%